Increased pulsatility index is associated with adverse outcomes in left ventricular assist device recipients. (4th August 2021) - Tucanova, Zuzana; Ivak, Peter; Wohlfahrt, Peter; Pol, Marek; Hlavacek, Daniel; Konarik, Miroslav; Szarszoi, Ondrej; Netuka, Ivan; Pitha, Jan
Abstract: Aims: Recipients of left ventricular assist devices (LVAD) are exposed to increased risk of adverse clinical events. One of the potential contributing factors is non‐pulsatile flow generated by LVAD. We evaluated the association of flow patterns in carotid arteries and of increased arterial stiffness with death and cerebrovascular events in LVAD recipients. Methods and results: We analysed data from 83 patients [mean age 54 ± 15 years; 12 women; HeartMate II (HMII), n = 34; HeartMate 3 (HM3), n = 49]. Pulsatile and resistive indexes, atherosclerotic changes in carotid arteries (measured by duplex ultrasound), and arterial stiffness [measured by Endo‐PAT 2000 as the augmentation index standardized for heart rate (AI@75)] were evaluated 3 and 6 months after LVAD implantation. Sixteen patients died during follow‐up (27.3 months; interquartile range 15.7–44.3). After adjusting for the main variables examined, the pulsatility index measured at 3 months was positively associated with increased hazard ratios (HR) for death and cerebrovascular events [HR 9.8, 95% confidence interval (CI) 1.62–59.42], with HR increasing after adding AI@75 to the model (HR 18.8, 95% CI 2.44–145.50). In HM3 recipients, HR was significantly lower than in HMII recipients (HR 0.31, 95% CI 0.11–0.91), but the significance disappeared after adding AI@75 to the model (HR 0.33, 95% CI 0.09–1.18). Conclusions: The risk of death and cerebrovascular events in LVAD recipients is associated with increased pulsatility index in carotid arteries and potentiated by increased arterial stiffness. The same risk is attenuated by HM3 LVAD implantation, but this effect is weakened by increased arterial stiffness.